Penerapan Perubahan Dalam Peningkatan Teknologi Absensi Pekerja - Fakri Mursala; Nuri Aslami (Jurnal Manajemen Akuntansi (JUMSI), 2022)
The presence of employees is an important factor for an agency or company to achieve its goals. This is disciplined and affects the performance of each employee. Therefore, special data collection is needed for recording attendance and absenteeism in order to be able to record work activities quickly and accurately. There are many ways to achieve a good attendance information system, one of which is by using computer technology when the application is a website-based attendance application using either a Qr code, fingerprint, or biometrics. positive for employees and the company. The purpose of this study is to find out more about the development of changes in the attendance system of workers to do work and what are the benefits for companies to use the digital attendance system. The method used in the application of this research is qualitative-based research by utilizing secondary data obtained indirectly through a literature review.